Surgeon‐performed ultrasound changes surgical management in patients with thyroid cancer. Issue 12 (24th September 2022) - Tapia, Mario; Chia, Clemente; Manji, Jamil; Magarey, Matthew J. R.; Flatman, Samuel
Abstract: Background: A comprehensive neck ultrasound (US) is essential in the operative planning of patients with thyroid disease. Recent literature has shown surgeon‐performed US (SUS) can be more accurate than radiology‐performed US for the purpose of surgical planning. Missed findings on radiology‐performed ultrasound may lead to inadequate surgical management. Methods: A retrospective cohort study of patients undergoing total thyroidectomy with lateral neck dissection for thyroid cancer, with both radiology‐performed US and SUS performed by a Head and Neck surgeon. Ultrasound findings and adherence to American Thyroid Association (ATA) guidelines were compared, and changes in management based on SUS findings were identified. Results: A total of 26 patients who underwent total thyroidectomy with lateral neck dissection met the inclusion criteria. Preconsultation US investigations fulfilled criteria as recommended by the American Thyroid Association (ATA) guidelines in 57.7%% of cases. The central and lateral neck compartments were assessed in 57.7% and 84.6% of preconsultation US investigations respectively. Central and lateral metastatic neck metastases were incorrectly reported or not reported in 78.6% and 42.3% of cases. The SUS findings prompted a change in surgical management in 65.4% of cases. Conclusion: SUS changed surgical management in two thirds (65.4%) of patients. Reliance on radiology‐performed ultrasound alone may result in incorrect staging. Awareness of the additional benefits of SUS is important for surgeons treating patients with thyroid disease to prevent inadequate surgery being performed. Abstract : Literature has shown surgeon‐performed ultrasound (SUS) can identify findings missed on radiology‐performed US that may le to inadequate surgical management. This is a retrosective cohort study of patients undergoing total thyroidectomy with lateral neck dissection for thyroid cancer, with both radiology‐performed ultrasound and ultrasound performed by a head and neck surgeon. Findings on surgeon‐performed ultrasound that were not present on radiology‐performed ultrasound changed surgical management in 65.4% of cases.